Design Low Noise Digital Decimation Filter For Sigma-Delta-ADC (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper focuses on the design of digital decimation filter for single bit Sigma-Delta A/Dconverter with medium oversampling ratio for the processing of audio and biomedical signal. A second-order single-stage sigma-delta (Σ-Δ) modulator with single bit quantizer with oversampling ratio 96 workas a basic modulator. For hardware requirement, multiplier less CIC compensation FIR filter architectureused. Total three CIC compensation filter are used for decimation and filtering purpose. All filters are designed and simulated with MATLAB